Hambatan yang Dihadapi Siswa dalam Menguasai Kosakata Bahasa Inggris di MTs Al-Hidayah, Desa Beringin Lestari, Kecamatan Tapung Hilir, Kabupaten Kampar - Candra Kirana (EL-EMIR Institute, 2025)
This research aims to identify and analyze the obstacles faced by students in practicing English communication at MTs Al-Hidayah, Beringin Lestari Village, Tapung Hilir District, Kampar Regency. Mastery of English is not solely dependent on vocabulary or grammar comprehension but also on students' ability to use it in daily communication. However, many students encounter challenges in practicing direct communication, as reflected in their lack of confidence and limited opportunities to use English within and outside the school environment. The research employed a descriptive qualitative method with interviews, observations, and document analysis as the primary approaches. The findings reveal that the main barriers include limited opportunities for direct communication practice, overly theoretical teaching methods, and insufficient support from the learning environment. Students also struggle to integrate the vocabulary and grammar they have learned into daily conversations. This study recommends a more practice-oriented teaching approach through conversation simulations, group discussions, and language games. Additionally, utilizing technology such as interactive communication apps and educational videos can enhance students' communication skills. Community involvement in creating an English-speaking environment also serves as an essential supporting factor. By implementing these strategies, students are expected to overcome obstacles in practicing English communication, leading to significant improvements in their language skills.